In Operando Probing of Lithium‐Ion Storage on Single‐Layer Graphene. Issue 23 (11th April 2019) - Ni, Kun; Wang, Xiangyang; Tao, Zhuchen; Yang, Jing; Shu, Na; Ye, Jianglin; Pan, Fei; Xie, Jian; Tan, Ziqi; Sun, Xuemei; Liu, Jie; Qi, Zhikai; et al.
Abstract: Despite high‐surface area carbons, e.g., graphene‐based materials, being investigated as anodes for lithium (Li)‐ion batteries, the fundamental mechanism of Li‐ion storage on such carbons is insufficiently understood. In this work, the evolution of the electrode/electrolyte interface is probed on a single‐layer graphene (SLG) film by performing Raman spectroscopy and Fourier transform infrared spectroscopy when the SLG film is electrochemically cycled as the anode in a half cell. The utilization of SLG eliminates the inevitable intercalation of Li ions in graphite or few‐layer graphene, which may have complicated the discussion in previous work. Combining the in situ studies with ex situ observations and ab initio simulations, the formation of solid electrolyte interphase and the structural evolution of SLG are discussed when the SLG is biased in an electrolyte. This study provides new insights into the understanding of Li‐ion storage on SLG and suggests how high‐surface‐area carbons could play proper roles in anodes for Li‐ion batteries. Abstract : A single‐layer graphene film is electrochemically cycled as an anode in a half cell to probe the evolution of the electrode/electrolyte interface and lithium‐storage mechanism, which are followed by in operando Raman spectroscopy and Fourier transform infrared spectroscopy. The understanding may provide new insight on the Li deposition on carbon and the role of high‐specific‐surface‐area carbons as anodes for Li‐ion batteries.